(untitled) (Üçüncü Sektör Sosyal Ekonomi Dergisi, 2025)
The aim of this paper is to analyze the effect of remittances on economic growth in Türkiye in the context of financial development. The model of this study is compiled from annual data between 1980 and 2023. It uses variables relating to economic growth, the level of financial development and remittances, as well as a control variable consisting of trade openness. The A-ARDL (augmented autoregressive distributed lag bounds) method is used to determine whether there is any cointegration relationship between these variables. In addition to ARDL long-run coefficient estimators, FMOLS, DOLS and CCR coefficient estimators are also used. In addition, Toda-Yamamoto (1995) causality test was applied to determine the existence of causality between the variables. According to the findings obtained from the A-ARDL method, all three variables are cointegrated with economic growth. According to the ARDL long-run coefficient results, a 1% increase in financial development leads to an increase of approximately 0.22% in economic growth, while a 1% increase in trade openness leads to an increase of approximately 0.53% in economic growth. However, a 1% increase in remittances causes a decrease of approximately 0.12% in economic growth. FMOLS, DOLS and CCR estimators show that a 1% increase in remittances decreases economic growth by about 0.14%; a 1% increase in financial development increases economic growth by about 0.18%; and a 1% increase in the control variable, trade openness, increases economic growth by about 0.43%. That is, remittances are negatively correlated with economic growth, while financial development is positively correlated with economic growth. Moreover, Toda-Yamamoto (1995) causality tests revealed that there is a bidirectional causality relationship between economic growth and financial development and a unidirectional causality relationship from remittances to economic growth.